Biblical parallels and biblical Hebrew syntax - Zewi, Tamar (Zeitschrift für Althebraistik, 2004)
Biblical parallels have long been subject to investigation and research in several disciplines. Biblical scholars have usually been interested in the differences that parallels exhibit in content and vocabulary. Syntactic variations revealed in biblical parallels are usually woven into other syntactic discussions and have not yet acquired the attention they deserve. The aim of the paper is to present meaningful biblical Hebrew syntactic variations that occur in biblical parallels and linguistically to analyze the distinctions they provide.